Localization of male-specifically expressed MROS genes of Silene latifolia by PCR on flow-sorted sex chromosomes and autosomes - Kejnovský, E; Vrána, J; Matsunaga, S; Soucek, P; Siroký, J; Dolezel, J; Vyskot, B (Genetics, 2001)
The dioecious white campion Silene latifolia (syn. Melandrium album) has heteromorphic sex chromosomes, XX in females and XY in males, that are larger than the autosomes and enable their separation by flow sorting. The group of MROS genes, the first male-specifically expressed genes in dioecious plants, was recently identified in S. latifolia. To localize the MROS genes, we used the flow-sorted X chromosomes and autosomes as a template for PCR with internal primers. Our results indicate that the MROS3 gene is located in at least two copies tandemly arranged on the X chromosome with additional copy(ies) on the autosome(s), while MROS1, MROS2, and MROS4 are exclusively autosomal. The specificity of PCR products was checked by digestion with a restriction enzyme or reamplification using nested primers. Homology search of databases has shown the presence of five MROS3 homologues in A. thaliana, four of them arranged in two tandems, each consisting of two copies. We conclude that MROS3 is a low-copy gene family, connected with the proper pollen development, which is present not only in dioecious but also in other dicot plant species.
Keywords: sekvence nukleotidů; DNA primery; sekvenční homologie aminokyselin; Sex Chromosomes; Magnoliopsida; pohlavní chromozomy; Sequence Homology, Amino Acid; Molecular Sequence Data; In Situ Hybridization, Fluorescence; molekulární sekvence - údaje; Amino Acid Sequence; rostlinné geny; Genes, Plant; Base Sequence; hybridizace in situ fluorescenční; rostlinné proteiny; polymerázová řetězová reakce; DNA Primers; Polymerase Chain Reaction; Plant Proteins; sekvence aminokyselin